Exploring linear algebra : labs and projects with Matlab - Arangala, Crista (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This text is meant to be a hands-on lab manual that can be used in class everyday to guide the exploration of the theory and applications of linear algebra. For the most part, labs can be used individually or in a sequence. Each lab consists of and explanation of material with integrated exercises. Some labs are split into multiple subsections and thus exercises are separated by those subsections.The exercise sections integrate problems using Mathematica demonstrations (an online tool that can be used with an browser with java capabilities) and Matlab coding. This allows students to discover the theory and applications of linear algebra in a meaningful and memorable way
OCLC-licensed vendor bibliographic record.
Keywords: MATLAB; Algebras, Linear -- Computer-assisted instruction; MATHEMATICS / Algebra / Intermediate; MATHEMATICS / General; MATHEMATICS / Algebra / General; MATHEMATICS / Applied